RIYA' IN THE REALM OF SOCIAL MEDIA (AN EXAMINATION OF THE INTERPRETATION OF THE WORKS OF WAHBAH AZ-ZUHAILI AND M. QURAISH SHIHAB) - Hartono, Hartono; Izzaniyah, Faiqo (UIN Mataram, 2023)
Abstract: The purpose of this research is to provide understanding to all people regarding riya' which always perches in every human heart. Riya', not many people know, including himself, who has riya in his heart. The benefits of this research are also expected to minimize and eliminate riya behavior. Because basically the behavior of riya' or those who always want to be seen more by others can happen to anyone, doing everything is not because of Allah SWT even though in appearance it feels religious. Riya' becomes a heart disease and will give birth to other heart diseases such as ujub, takabbur, envy and envy. This research method uses literature research and social analysis through social media from various social media platforms. Keyword: riya’ dan media social, Wahbah Az-zuhaili dan M. Quraish Shihab